Trends in time to invasive examination and treatment from 2001 to 2009 in patients admitted first time with non-ST elevation myocardial infarction or unstable angina in Denmark. Issue 1 (9th January 2014) - Mårtensson, Solvej; Gyrd-Hansen, Dorte; Prescott, Eva; Andersen, Per Kragh; Zwisler, Ann-Dorthe Olsen; Osler, Merete
Abstract : Objective: To investigate trends in time to invasive examination and treatment for patient with first time diagnosis of non-ST elevation myocardial infarction (NSTEMI) and unstable angina during the period from 2001 to 2009 in Denmark. Design: From 1 January 2001 to 31 December 2009 all first time hospitalisations with NSTEMI and unstable angina were identified in the National Patient Registry (n=65 909). Time from admission to initiation of coronary angiography (CAG), percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) was calculated. We described the development in invasive examination and treatment probability (CAG, PCI and CABG at 3, 7, 10, 30 and 60 days) for the years 2001–2009, taking the competing risk of death into account using Aalen–Johansen estimators and a Fine-Gray model. Setting: Nationwide Danish cohort. Results: The proportion of patients receiving a CAG and PCI increased substantially over time while the proportion receiving a CABG decreased for both NSTEMI and unstable angina. For both NSTEMI and unstable angina, a significant increase in invasive examination and treatment probability at 3 days for CAG and PCI were seen especially from 2007 through to 2009. For NSTEMI, the CAG examination probability at 3 days leaped from 20% in 2007 to 32% in 2008 and 39% in 2009, and for PCI the same was true with a leap in treatment probability from 19% to 28% from 2008 to 2009. Conclusions: In Denmark the use of CAG and PCI in treatment of NSTEMI and unstable angina has increased from 2001 to 2009, while the use of CABG has decreased. During the same period, there was a marked increase in invasive examination and treatment probability at 3 days, that is, more patients were treated faster which is in line with the political aim of reducing time to treatment.